Social space in the urban network of Rio de Janeiro - Geiger, Pedro Pinchas (GEOUSP Espaço e Tempo (Online), 2000)
The present work pretends to bring a little contribution to the cnowledge of the geography of Rio de Janeiro (Brazil and sim ultaneously, to participate of the revival of the debate about the utilization of quantitative methods in geographic works